Development and evaluation of the psychometric properties of a brief parenting scale (PS-7) for the parents of adolescents. - Sai-Fu Fung; Annis Lai Chu Fung (PLoS ONE, 2020)
This study aimed to develop a seven-item brief parenting scale (PS-7) based on the original parenting scale (PS) and various other shortened versions and with a better factor structure for the parents of adolescents. The scale was tested with a sample of 3,777 parents (2,205 mothers and 1,572 fathers). Confirmatory factor analysis was used to evaluate the dimensionality of the different versions of the PS. Only the PS-7 with a two-factor structure, i.e., laxness (three items) and overreactivity (four items), showed a good model fit based on a representative sample of parents of junior secondary school students. Overall, the results suggest that PS-7 is comparable to the original PS and possesses good psychometric properties in terms of internal consistency, factorial validity, construct validity, criterion validity and discriminant validity. The abbreviated parenting scale also provides a reliable and cost-effective method for assessing parental practices for treatment and assessing treatment outcomes.